The pharmacokinetics profiles, pharmacological properties, and toxicological risks of dehydroevodiamine: A review - Fu, Shubin; Liao, Liying; Yang, Yi; Bai, Yan; Zeng, Yan; Wang, Haoyu; Wen, Jianxia (Frontiers in Pharmacology, 2022)
Dehydroevodiamine (DHE) is a quinazoline alkaloid isolated from Evodiae Fructus (EF, Wuzhuyu in Chinese, Rutaceae family), a well-known traditional Chinese medicine (TCM) which is clinically applied to treat headache, abdominal pain, menstrual pain, abdominal distension, vomiting, acid regurgitation, etc. Modern research demonstrates that DHE is one of the main components of EF. In recent years, DHE has received extensive attention due to its various pharmacological activities. This review is the first to comprehensively summarize the current studies on pharmacokinetics profiles, pharmacological properties, and toxicological risks of DHE in diverse diseases. Pharmacokinetic studies have shown that DHE has a relatively good oral absorption effect in the mean concentration curves in rat plasma and high absorption in the gastrointestinal tract. In addition, distribution re-absorption and enterohepatic circulation may lead to multiple blood concentration peaks of DHE in rat plasma. DHE possesses a wide spectrum of pharmacological properties in the central nervous system, cardiovascular system, and digestive system. Moreover, DHE has anti-inflammatory effects via down-regulating pro-inflammatory cytokines and inflammatory mediators. Given the favorable pharmacological activity, DHE is expected to be a potential drug candidate for the treatment of Alzheimer’s disease, chronic stress, amnesia, chronic atrophic gastritis, gastric ulcers, and rheumatoid arthritis. In addition, toxicity studies have suggested that DHE has proarrhythmic effects and can impair bile acid homeostasis without causing hepatotoxicity. However, further rigorous and well-designed studies are needed to elucidate the pharmacokinetics, pharmacological effects, potential biological mechanisms, and toxicity of DHE.